Aluminum-based lithium adsorbent, polyacrylamide-based high-hydrophilic membrane and hydrophilic loading method and application of polyacrylamide-based high-hydrophilic membrane

By using a continuous flow reactor and natural sugar macromolecules in the aluminum-based lithium adsorbent process, a polyacrylamide-based high hydrophilic film loaded with aluminum-based lithium adsorbent was prepared, which solved many problems of the existing adsorbents in the lithium extraction process, and achieved a more efficient and stable Li+ adsorption and extraction effect.

CN119701861APending Publication Date: 2025-03-28TIANJIN UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411934745.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the lithium extraction process, the existing aluminum-based lithium adsorbents have problems such as difficult to control the particle size, easy loss of LDH powder, low adsorption capacity, easy collapse of structure, and poor adaptability to the environment.

Method used

Aluminum-based lithium adsorbent powder is prepared by a continuous flow reactor, and the particle size distribution is controlled by adjusting the concentration and flow rate of the raw material solution. At the same time, natural sugar macromolecular powder was added to promote the uniform distribution of the adsorbent in the film, and a polyacrylamide-based high hydrophilic film loaded with aluminum-based lithium adsorbent was prepared.

Benefits of technology

The uniformity of the particle size distribution of aluminum-based lithium adsorbent is achieved, the adsorption amount and extraction efficiency of Li+ are improved, the mechanical strength and water absorption of the film are enhanced, and the stability of use in complex brine environments is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701861A_ABST
    Figure CN119701861A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of adsorbents, and relates to an aluminum-based lithium adsorbent, a polyacrylamide-based high-hydrophilic membrane, a hydrophilic loading method of the polyacrylamide-based high-hydrophilic membrane and application of the polyacrylamide-based high-hydrophilic membrane. And the novel polyacrylamide-based polymer hydrophilic membrane which is of a three-dimensional network porous structure and is loaded with the aluminum-based lithium adsorbent is successfully prepared, the elongation of the membrane is 1500-2000%, the tensile strength of the membrane is 0.5-0.6 Mpa, and the membrane has relatively high water absorption, high lithium adsorption capacity and high lithium extraction efficiency and can be used for extracting lithium resources in salt lake brine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorbents, and relates to an aluminum-based lithium adsorbent, a polyacrylamide-based highly hydrophilic membrane, and a hydrophilic loading method and application thereof. Background Art

[0002] Aluminum-based lithium adsorbents have an advantageous position in the lithium extraction industry of salt lakes and are currently the only industrialized adsorbents. In the lithium extraction process, adsorbents for adsorption are divided into two categories: inorganic and organic. Organic adsorbents have poor selectivity and are difficult to elute. Although titanium-based / manganese-based ion sieves in inorganic adsorbents have advantages, desorption depends on acid washing, resulting in adsorbent dissolution loss and cycle life decay. Aluminum-based lithium adsorbents have the advantages of using water to elute lithium, stable structure, simple synthesis, and high Li+ selectivity to achieve large-scale industrial application. However, the existing adsorbent preparation process is difficult to control the LDH particle size, and LDH powder adsorption is easy to lose during the cyclic adsorption process. In industry, the cross-linking-bonding effect of organic polymer materials is commonly used to granulate the adsorbent powder. Commonly used organic polymer adhesives include polyvinyl chloride (PVC), polyvinylidene fluoride (PVDF), etc. The adsorbent after granulation is screened to remove unqualified particles to ensure that the particles are uniform and regular, so as to ensure good filling and fluid permeability in the fixed column. Fixed bed chromatographic columns can provide continuous cycle operation and are easy to scale up. Their comprehensive lithium extraction effect is better than intermittent operation, which can improve production efficiency and product quality.

[0003] As the core material, the aluminum-based lithium adsorbent layer structure and load fixation method determine its application effect in lithium extraction from salt lakes. At present, there are some defects and shortcomings in the industrial application of aluminum-based lithium adsorbents.

[0004] In terms of synthesis technology, among the common synthesis and preparation methods of aluminum-based lithium adsorbents, the disadvantage of the hydrothermal method is that it requires high-energy consumption steps such as high temperature and high pressure, and is highly dependent on production equipment. The equipment is generally in a closed container, and the crystal growth cannot be observed visually, and in-situ testing cannot be performed. There are often multiple accidental error factors in each product preparation, and the repeatability is low. The disadvantage of the co-precipitation method is that the addition of alkaline precipitants may cause the local concentration to be too high, resulting in agglomeration or uneven composition. During the process, alkaline solution needs to be continuously added to maintain pH. The mixing process of metal salts and alkaline solutions is long, and the crystal nuclei formed at the beginning of the addition process require longer aging time than at the end. It is difficult to control the particle size and distribution of LDHs, resulting in different performance of each batch of products.

[0005] In terms of adsorption performance, the adsorption capacity of aluminum-based adsorbents used in industry is usually less than 3 mg (Li+) / g, which is far lower than the theoretical adsorption capacity, which severely limits its lithium extraction efficiency. In addition, the adsorbent structure is prone to collapse after multiple adsorption and desorption cycles. When eluting lithium in deionized water at 80°C, Li / Al-LDH will gradually collapse into gibbsite (α-Al(OH)3), further reducing the adsorption capacity of Li+ and affecting its long-term lithium extraction effect.

[0006] In the immobilization process, some active site embedding and deactivation problems will occur after conventional bonding granulation. The binder used in the granulation process will embed the active sites, resulting in a decrease in adsorption. Commonly used organic polymer adhesives such as polyvinyl chloride (PVC) can easily block the brine mass transfer channel, reduce the bed pressure drop, and reduce the effective contact surface area and the number of active sites of the adsorbent, making the adsorption capacity only about 40% of the powder, and there is still a continuous and small LDH dissolution loss. In addition, aluminum-based adsorbents also have the problem of poor environmental adaptability. It is not resistant to highly alkaline salt lake brine, and has large dissolution losses, resulting in deviations in the versatility of salt lakes, limiting its application in different salt lake environments. Summary of the invention

[0007] The purpose of the present invention is to overcome the shortcomings of the prior art, provide an aluminum-based lithium adsorbent, a polyacrylamide-based highly hydrophilic membrane and a hydrophilic loading method and application thereof, for the first time adopt a continuous flow reactor to simply and efficiently prepare an aluminum-based lithium adsorbent, and successfully prepare a new polyacrylamide-based polymer hydrophilic membrane loaded with an aluminum-based lithium adsorbent, which is used for lithium resource extraction in salt lake brine, thereby improving the Li + adsorption capacity and extraction efficiency.

[0008] The technical solution adopted by the present invention to solve the technical problem is:

[0009] The idea of ​​the method of the present invention is as follows: through continuous flow reaction equipment, a suitable flow channel is designed to prepare aluminum-based lithium adsorbent powder. The prepared aluminum-based lithium adsorbent powder material is added to a hydrophilic polymer mixed liquid to adjust the ratio and prepare a liquid casting film. By adjusting the dosage ratio and the thickness of the casting film, the hydrophilic film is loaded with uniformly dispersed aluminum-lithium adsorbent powder.

[0010] The first aspect of the present invention provides an aluminum-based lithium adsorbent, the adsorbent has a uniform particle size distribution, a particle size of 2μm-50μm, and a lithium adsorption capacity of 4-7mg / g.

[0011] Furthermore, the preparation method is as follows: using a continuous flow reactor, using a horizontal flow pump to control the flow rate of the raw materials, mixing solution A and solution B at a constant temperature of 20-80°C for continuous reaction, collecting the precipitate, and centrifugally freeze-drying to obtain a uniform aluminum-based lithium adsorbent, wherein solution A is a mixed solution of aluminum salt and lithium salt, and Li in solution A is+ 、Al 3+ The concentration is 0.5-10 mol / L, and solution B is 0.05-20 mol / L sodium hydroxide solution. The particle size of the product is controlled by the concentration of aluminum salt and lithium salt, stirring rate and temperature (100nm-50μm).

[0012] Furthermore, the solution A is doped with 0.1-4 mol / L of a divalent and / or trivalent metal salt solution.

[0013] Furthermore, the flow rates of solution A and solution B are 0.1-10 mL / min, and the flow rate ratio of solution A to solution B is 1:0.4-1:1.

[0014] Furthermore, the volume ratio of solution A to solution B is 1-2.5.

[0015] The second aspect of the present invention provides a method for hydrophilic loading of the aluminum-based lithium adsorbent, comprising:

[0016] (1) mixing acrylamide and the eluted aluminum-based lithium adsorbent, adding them to deionized water, stirring continuously, and adding an initiator and a cross-linking agent to form a solution C; the aluminum-based lithium adsorbent, the initiator, and the cross-linking agent account for 0.1-50%, 0.12-0.66%, and 0.08-1% of the mass of acrylamide, respectively;

[0017] (2) adding natural sugar macromolecule powder to solution C, stirring until the natural sugar macromolecule powder is completely dissolved in the solution to obtain a casting solution, ultrasonicating the casting solution, and then vacuum degassing to form a uniform casting solution; the natural sugar macromolecule powder accounts for 1.5-15% of the mass of acrylamide; the natural sugar macromolecule is one or more of xanthan gum, water-soluble starch, gelatin, carrageenan, and sodium alginate;

[0018] (3) adding the casting liquid into the mold, drying or UV irradiation, cross-linking and curing to obtain a cured film; the film thickness range is 0.1-5 mm; the mold is a transparent and encapsulable mold, and the film thickness is controlled by the mold;

[0019] (4) The cured film is taken out, immersed in deionized water, and dried to obtain a polyacrylamide-based highly hydrophilic film loaded with an aluminum-based lithium adsorbent.

[0020] Furthermore, the natural sugar macromolecular powder accounts for 5-10% of the mass of acrylamide.

[0021] Furthermore, the initiator is a thermal initiator or a photoinitiator, the thermal initiator is one or more of potassium persulfate, sodium persulfate, and ammonium persulfate, and the photoinitiator is an aqueous photoinitiator selected from one or more of 1173, 8700, and LAP.

[0022] Furthermore, the cross-linking agent is one or more of a bisacryl cross-linking agent, a dialdehyde cross-linking agent, and N,N'-methylenebisacrylamide (MBAA); the bisacryl cross-linking agent is selected from one or more of N,N'-methylenebisacrylamide, dipropylene glycol methyl ether, acrylamide-polyethylene glycol-acrylamide, and N,N'-bis(acryloyl)cystamine; and the dialdehyde cross-linking agent is selected from one or more of succinaldehyde, glutaraldehyde, and adipic dialdehyde.

[0023] Furthermore, in step (3), the mixture is placed in an oven at 40-80° C. for 0.5-12 hours for drying or irradiated under ultraviolet light for 0.01-1 hour.

[0024] In this application, the added carbohydrate macromolecules, by virtue of their abundant hydroxyl groups, are closely connected to the active sites on the surface of the aluminum-based lithium adsorbent through hydrogen bonding, and this interaction effectively prevents the agglomeration of the adsorbent particles, laying the foundation for its uniform dispersion. At the same time, the space occupied by the carbohydrate macromolecules in the solution forms a steric hindrance effect, making it difficult for the adsorbent particles to approach each other and maintain a certain spacing, further ensuring a uniformly dispersed state. And it and the polyacrylamide cross-linked network semi-interpenetrating collaboratively construct a three-dimensional network structure, so that the aluminum-based lithium adsorbent can be efficiently and stably loaded on the film, thereby optimizing the performance and function of the entire system. At the same time, due to the large amount of hydroxyl groups contained in the carbohydrate macromolecules, they can not only make the membrane surface quickly wetted by water, but also interweave with the polyacrylamide molecular chain inside the membrane, creating a continuous hydrophilic environment, so that the contact between the adsorbent particles and the brine can be accelerated in the real brine environment, reducing the problem of loss of adsorption active sites caused by other load substrates. In terms of mechanical strength, carbohydrate macromolecules are flexible and stretchable, forming physical entanglements and hydrogen bonds with polyacrylamide molecular chains. When the membrane is subjected to tensile force, they act like "springs" to buffer the stretching, allowing the molecular chains to stretch and slide more freely, effectively resisting external forces, thereby improving mechanical strength and allowing polyacrylamide-based highly hydrophilic membranes to perform better in actual adsorption applications.

[0025] The third aspect of the present invention provides a polyacrylamide-based highly hydrophilic membrane loaded with an aluminum-based lithium adsorbent prepared by the above-mentioned hydrophilic loading method, characterized in that the interior of the membrane is a three-dimensional network porous structure, the aluminum-based lithium adsorbent is evenly distributed in the membrane, the lithium adsorption capacity is 4-7 mg / g, the elongation is 1500% to 2000%, the tensile strength is 0.5 to 0.6 MPa, and the water absorption rate is 700% to 800%.

[0026] The fourth aspect of the present invention provides the polyacrylamide-based highly hydrophilic membrane loaded with aluminum-based lithium adsorbent for brine adsorption or Li adsorption in combination with adsorption column process. + Separation application.

[0027] Furthermore, a suitable amount of polyacrylamide-based highly hydrophilic membrane loaded with adsorbent is taken and filled into the adsorption column in a layered manner. At 20-80°C, a peristaltic pump is used to pump the Li-containing solution from bottom to top at a flow rate of 1-20 mL / min. + The concentration of brine is 0.1-2g / L, until the lithium concentration of the solution collected at the outlet no longer changes, the membrane is taken out, placed in deionized water, and stirred in a constant temperature water bath at 20-80℃ to elute the Li + .

[0028] The advantages and positive effects of the present invention are:

[0029] (1) The present invention adopts a continuous flow reaction device to prepare an aluminum-based lithium adsorbent powder material with uniform particle size distribution. By adjusting the concentration of the starting raw material solution, the particle size of the product can be controlled. It is not necessary to synthesize and prepare in a closed container, so that the structure and performance of the material can be sampled and tested at any time, so as to adjust the process and improve the material at any time. Since continuous preparation is possible, the parameters can be adjusted to make the product uniform and consistent in performance each time, which is convenient for mass production.

[0030] (2) The present invention promotes the uniform distribution of aluminum-based lithium adsorbent in the membrane by adding natural sugar macromolecular powder. The prepared three-dimensional network porous structure of polyacrylamide-based high-hydrophilic membrane loaded with aluminum-based lithium adsorbent has high elongation (elongation 1500% to 2000%), mechanical strength (tensile strength 0.5 to 0.6Mpa), and high water absorption (water absorption 700% to 800%). These properties can make it more stable to use in complex brine environments.

[0031] (3) The polyacrylamide-based highly hydrophilic membrane loaded with aluminum-based lithium adsorbent prepared by the present invention improves the Li + The adsorption and extraction efficiency of the adsorbent powder is generally about 0.5h. After the general granulation method, the adsorption saturation time increases to several hours to dozens of hours. The membrane adsorption material loaded with the high hydrophilic membrane has high hydrophilicity and good dispersibility of the adsorbent particles, which reduces the Li + The adsorption is hindered during its migration to the adsorbent particles, and adsorption saturation is generally reached within 1-2 hours.

[0032] (4) The polyacrylamide-based highly hydrophilic membrane loaded with aluminum-based lithium adsorbent prepared by the present invention improves the Li + The adsorption capacity is due to the high water absorption of the highly hydrophilic membrane, which makes the polymer chain embedding the adsorbent particles and the Li + The problem of reduced adsorption active sites has been greatly improved. The lithium adsorption capacity after industrial granulation is about 3 mg / g. The lithium adsorption capacity of the high hydrophilic membrane adsorption material (attachedFigure 5 ) can reach about 4-7 mg / g (converted into the amount of powdered adsorbent). BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 XRD diagram of the aluminum-based lithium adsorbent prepared in Example 1 and Example 2;

[0034] Figure 2 TEM image of the polyacrylamide-based highly hydrophilic membrane with a Li-Al-LDH loading of 10% prepared in Example 1;

[0035] Figure 3 This is a particle size distribution diagram of the aluminum-based lithium adsorbent prepared in Example 1;

[0036] Figure 4 The polyacrylamide-based highly hydrophilic membrane with a Li-Al-LDH loading of 10% prepared in Example 1 was + Static adsorption data graph in pure lithium chloride solution with a concentration of 0.8 g / mol;

[0037] Figure 5 This is the SEM image of the polyacrylamide-based highly hydrophilic membrane with a Li-Al-Fe-LDH loading of 10% prepared in Example 2. DETAILED DESCRIPTION

[0038] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0039] Example 1

[0040] A method for preparing an aluminum-based lithium adsorbent comprises:

[0041] Prepare 1.2 mol / L lithium chloride and 1.5 mol / L aluminum chloride, take 100 mL of each and mix to obtain solution A, prepare 5 mol / L sodium hydroxide solution (solution B); continue mixing and reacting at a constant temperature of 40° C. in a continuous flow reactor, with the flow rates of solutions A and B being 5 mL / min and 3.5 mL / min, respectively; collect the precipitate, centrifuge and freeze-dry to obtain a uniform aluminum-based lithium adsorbent (Li-Al-LDH) powder. The XRD pattern of the aluminum-based lithium adsorbent prepared in Example 1 is as follows Figure 1 As shown in the TEM image Figure 2 As shown, the particle size distribution of the product is 2μm–50μm. Figure 3 As shown;

[0042] The hydrophilic loading method of the aluminum-based lithium adsorbent prepared in Example 1 comprises:

[0043] Mix 3g acrylamide and 0.3g of the prepared aluminum-based lithium adsorbent powder in a beaker, add 20mL of deionized water, continue stirring, add 3.6mg of thermal initiator ammonium persulfate, and 2.4mg of cross-linking agent MBAA, stir evenly to form solution C, then add 0.15g of xanthan gum and stir for 2 hours until the powder is completely dissolved in the solution to obtain a casting solution, ultrasonic for 20 minutes, and then vacuum degassing, add the casting solution to a 20mm*20mm*0.5mm transparent encapsulable mold and place it in a 50℃ oven for 2 hours to cross-link and solidify into a film. Take out the cured film and soak it in deionized water to wash the residual impurities on the surface. After freeze drying, a polyacrylamide-based highly hydrophilic membrane with a Li-Al-LDH loading of 10% can be obtained.

[0044] The XRD pattern of Li-Al-LDH prepared in Example 1 is as follows Figure 1 TEM images are shown in Figure 2 The particle size distribution diagram of aluminum-based lithium adsorbent is shown in Figure 3 shown.

[0045] Example 2

[0046] A method for preparing an aluminum-based lithium adsorbent comprises: preparing 1.2 mol / L lithium chloride, 1.5 mol / L aluminum chloride, and 1.5 mol / L ferric chloride, taking 100 mL, 90 mL, and 10 mL of each solution and mixing them to obtain solution A, and preparing a 5 mol / L sodium hydroxide solution (solution B); performing a mixing reaction at a constant temperature of 40° C. in a continuous flow reactor, wherein the flow rates of solutions A and B are 5 mL / min and 3.5 mL / min, respectively; collecting a precipitate, centrifuging, freeze-drying, and obtaining a Li / Al-LDH adsorbent powder (Li-Al-Fe-LDH) with a Fe doping amount of 10%, wherein the particle size distribution of the product is 0.5 μm-50 μm; the XRD pattern of the Li-Al-Fe-LDH prepared in Example 2 is as follows: Figure 1 shown.

[0047] Example 2: The preparation method of the aluminum-based lithium adsorbent is the same as that of Example 1, except that a polyacrylamide-based highly hydrophilic membrane with a Li-Al-Fe-LDH loading of 10% is prepared. The SEM image is as follows: Figure 5 As shown, it can be seen that the aluminum-based lithium adsorbent is evenly distributed in the membrane, and the interior is a three-dimensional network porous structure.

[0048] Example 3

[0049] A method for preparing an aluminum-based lithium adsorbent is the same as in Example 1;

[0050] The hydrophilic loading method of the aluminum-based lithium adsorbent prepared in Example 3 comprises:

[0051] Mix 3g acrylamide and 0.3g of the prepared aluminum-based lithium adsorbent powder in a beaker, add 20mL of deionized water, continue stirring, add 15mg of photoinitiator 1173, and 2.4mg of crosslinker MBAA, stir evenly to form solution C, then add 0.15g of xanthan gum and stir for 2 hours until the powder is completely dissolved in the solution to obtain casting liquid A, ultrasonic for 20 minutes, and then vacuum degassing. Add casting liquid A to a 20mm*20mm*0.5mm mold and place it under a 395nm wavelength ultraviolet lamp for 10 minutes to form a film. Take out the cured film and soak it in deionized water to wash the residual impurities on the surface. After freeze drying, a polyacrylamide-based highly hydrophilic membrane with a Li-Al-LDH loading of 10% can be obtained.

[0052] Example 4

[0053] A method for preparing an aluminum-based lithium adsorbent is the same as in Example 1;

[0054] The hydrophilic loading method of the aluminum-based lithium adsorbent prepared in Example 4 comprises: mixing 3g of acrylamide and 0.3g of the prepared aluminum-based lithium adsorbent powder in a beaker, adding 20mL of deionized water, stirring continuously and adding 3.6mg of thermal initiator ammonium persulfate, and 2.4mg of cross-linking agent MBAA and stirring evenly to form solution C, followed by adding 0.2g of water-soluble starch, stirring for 2 hours until the powder is completely dissolved in the solution to obtain a mixed casting liquid A, ultrasonicating for 20 minutes, and then vacuum degassing. The casting liquid A is added to a 20mm*20mm*0.5mm mold and placed in a 50°C oven for 2 hours to form a film. The cured film is taken out and soaked in deionized water to wash away the residual impurities on the surface. After freeze drying, a polyacrylamide-based highly hydrophilic membrane with a Li-Al-LDH loading of 10% can be obtained.

[0055] Example 5

[0056] A method for preparing an aluminum-based lithium adsorbent is the same as in Example 1;

[0057] The hydrophilic loading method of the aluminum-based lithium adsorbent prepared in Example 5 comprises: mixing 3g acrylamide and 0.6g of the prepared aluminum-based lithium adsorbent powder in a beaker, adding 20mL of deionized water, stirring continuously and adding 3.6mg of thermal initiator ammonium persulfate, and 2.4mg of cross-linking agent MBAA and stirring evenly to form solution C, followed by adding 0.15g of xanthan gum and stirring for 2 hours until the powder is completely dissolved in the solution to obtain a mixed casting liquid A, ultrasonicating for 20 minutes, and then vacuum degassing. The casting liquid A is added to a 20mm*20mm*0.5mm mold and placed in a 50°C oven for 2 hours to form a film. The cured film is taken out and soaked in deionized water to wash the residual impurities on the surface. After freeze drying, a polyacrylamide-based highly hydrophilic membrane with a Li-Al-LDH loading of 10% can be obtained.

[0058] Comparative Example 1

[0059] The difference from Example 1 is that xanthan gum is not added in the hydrophilic loading method of the aluminum-based lithium adsorbent.

[0060] Comparative Example 2

[0061] The difference from Example 1 is that 0.01 g of xanthan gum is added in the hydrophilic loading method of the aluminum-based lithium adsorbent.

[0062] Comparative Example 3

[0063] The difference from Example 1 is that 0.8 g of xanthan gum is added in the hydrophilic loading method of the aluminum-based lithium adsorbent.

[0064] Adsorption test of polyacrylamide-based highly hydrophilic membranes prepared in Examples 1-6 and Comparative Examples 1-3: at 40°C, + The adsorption amount of static adsorption in pure lithium chloride solution with a concentration of 0.8 g / L (the adsorption amount of the highly hydrophilic membrane prepared in Example 1 is as follows Figure 4 shown); in Li + The simulated brine solution with a concentration of 0.2 g / L (C K +=3.52g / L,C Na + =90g / L, C Mg 2+ =11.42mg / L, C Ca 2+ =0.86 mg / L) in static adsorption, and the adsorption data are shown in Table 1.

[0065] Take an appropriate amount of polyacrylamide-based highly hydrophilic membrane with a Li-Al-LDH loading of 10%, and fill it into the adsorption column in a layered manner. Use a peristaltic pump to pump brine from bottom to top at a flow rate of 10mL / min until the lithium concentration of the solution collected at the outlet no longer changes. Take out the membrane, put it in deionized water, and stir in a constant temperature water bath at 20-80℃ to elute Li + The adsorption capacity of the polyacrylamide-based highly hydrophilic membrane was tested. The adsorption capacity of the adsorption column dynamic adsorption experiment with simulated brine of the same concentration was shown in Table 1.

[0066] The polyacrylamide-based highly hydrophilic membranes prepared in Examples 1-6 and Comparative Examples 1-3 were tested for mechanical properties and water absorption. The data are shown in Table 2.

[0067] Table 1 Adsorption data of polyacrylamide-based highly hydrophilic membranes prepared in Examples 1-6 and Comparative Examples 1-3

[0068]

[0069] As can be seen from Table 1, the various tests of Examples 1-5 have stable adsorption performance, indicating that the adsorption capacity has not increased exponentially, indicating that the types of adsorbents, the types of initiators, and the types of carbohydrate macromolecules to which this patent relates are all stable in performance. In Comparative Example 1, due to the absence of xanthan gum, the adsorbent is precipitated in the lower layer of the film during the static heating film-forming process of the mold, resulting in stacking agglomeration, and various adsorption test data show that the adsorption performance is greatly affected. Similarly, in Comparative Example 2, due to the less consumption of xanthan gum, the combination with the adsorbent is small, and the load dispersion effect is not good, and the stacking agglomeration phenomenon of the adsorbent in the gel is still serious. In Comparative Example 3, due to the excessive consumption of xanthan gum, although the adsorbent can be dispersed to the entire film, the local agglomeration is serious, and the shielding of a large number of adsorption sites is still caused, which affects the adsorption performance.

[0070] Table 2 Mechanical test and water absorption data of polyacrylamide-based highly hydrophilic membranes prepared in Examples 1-6 and Comparative Examples 1-3

[0071]

[0072]

[0073] According to the data comparison of Examples 1-5, it is shown that the type of adsorbent, the type of initiator, and the type of sugar macromolecule have no obvious effect on elongation, tensile strength and water absorption. Comparative Examples 1-3 show that the amount of sugar macromolecule added will affect the elongation, tensile strength and water absorption, thereby indirectly affecting the adsorption performance and adsorption effect.

[0074] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept, which all belong to the protection scope of the present invention.

Claims

1. An aluminum-based lithium adsorbent, characterized in that: The particle size is 100nm-50μm. The preparation method is as follows: a continuous flow reactor is used, a horizontal flow pump is used to control the flow rate of the raw materials, solution A and solution B are continuously mixed and reacted at a constant temperature of 20-80°C, the precipitate is collected, and centrifugal freeze-dried to obtain a uniform aluminum-based lithium adsorbent, wherein the solution A is a mixed solution of aluminum salt and lithium salt, and the Li in the solution A is + 、Al 3+ The concentration of solution A is 0.5-10mol / L, and the concentration of solution B is 0.05-20mol / L sodium hydroxide solution.

2. The aluminum-based lithium adsorbent according to claim 1, characterized in that The flow rate of solution A is 0.5-10 mL / min, and the flow rate of solution B is 0.5-10 mL / min.

3. The hydrophilic loading method of aluminum-based lithium adsorbent according to any one of claims 1 to 2, characterized in that: include: (1) mixing acrylamide and the eluted aluminum-based lithium adsorbent, adding them to deionized water, stirring continuously, and adding an initiator and a cross-linking agent to form a solution C; the aluminum-based lithium adsorbent, the initiator, and the cross-linking agent account for 0.1-50%, 0.12-0.66%, and 0.08-1% of the mass of acrylamide, respectively; (2) adding natural sugar macromolecule powder to solution C, stirring until the natural sugar macromolecule powder is completely dissolved in the solution to obtain a casting solution, ultrasonicating the casting solution, and then vacuum degassing to form a uniform casting solution; the natural sugar macromolecule powder accounts for 1.5-15% of the mass of acrylamide; the natural sugar macromolecule is one or more of xanthan gum, water-soluble starch, gelatin, carrageenan, and sodium alginate; (3) adding the casting liquid into the mold, drying or UV irradiation, cross-linking and curing to obtain a cured film; the film thickness ranges from 0.1 to 5 mm; (4) The cured film is taken out, immersed in deionized water, and dried to obtain a polyacrylamide-based highly hydrophilic film loaded with an aluminum-based lithium adsorbent.

4. The hydrophilic loading method according to claim 3, characterized in that: The solution A is doped with 0.1-4 mol / L of a divalent and / or trivalent metal salt solution.

5. The hydrophilic loading method according to claim 3, characterized in that: The natural sugar macromolecular powder accounts for 5-10% of the mass of acrylamide.

6. The hydrophilic loading method according to claim 3, characterized in that: The initiator is a thermal initiator or a photoinitiator, the thermal initiator is one or more of potassium persulfate, sodium persulfate, and ammonium persulfate, and the photoinitiator is an aqueous photoinitiator selected from one or more of 1173, 8700, and LAP.

7. The hydrophilic loading method according to claim 3, characterized in that: The cross-linking agent is one or more of a bisacryl cross-linking agent and a dialdehyde cross-linking agent, wherein the bisacryl cross-linking agent is selected from one or more of N,N'-methylenebisacrylamide, bisacryl glycol methyl ether, acrylamide-polyethylene glycol-acrylamide, and N,N'-bis(acryl)cystamine, and the dialdehyde cross-linking agent is selected from one or more of succinaldehyde, glutaraldehyde, and adipaldehyde.

8. The hydrophilic loading method according to claim 3, characterized in that: In step (3), the mixture is placed in an oven at 40-80° C. for 0.5-12 hours for drying or irradiated under ultraviolet light for 0.01-1 hour.

9. The polyacrylamide-based highly hydrophilic membrane loaded with aluminum-based lithium adsorbent prepared by the hydrophilic loading method according to any one of claims 3 to 8, characterized in that: The interior of the membrane is a three-dimensional mesh porous structure, and the aluminum-based lithium adsorbent is evenly distributed in the membrane. The lithium adsorption capacity is 4-7 mg / g, the elongation is 1500% to 2000%, the tensile strength is 0.5 to 0.6 Mpa, and the water absorption rate is 700% to 800%.

10. The polyacrylamide-based highly hydrophilic membrane loaded with aluminum-based lithium adsorbent according to claim 9 is used for Li adsorption in brine or combined with adsorption column process + Separation application.

Citation Information

Cited By

  • Negative pressure dust removal design and manufacturing method for multi-specification double-face milling equipment

    CN121004483A